Predicting time across age: comparing performance and neural dynamics of younger and older adults in a temporal prediction task. - Schoenfeld, Marleen J.; Burke, Rebecca; Schneider, Till R.; Engel, Andreas K. (Frontiers in Aging Neuroscience, 2026)
Temporal prediction is the ability to anticipate the likely time of occurrence of events and is important for adaptive behaviour in our everyday lives. Studies indicated that predictive aspects of environmental stimuli can be leveraged to reduce reaction times and enhance stimulus processing. Particularly, a recent study showed that this optimized behaviour is associated with a phase adjustment of ongoing neural oscillations aligning with the expected onset of upcoming stimuli. In ageing, there is some evidence that temporal predictions might be altered, however findings are inconsistent. Thus, we aimed to explore whether and how anticipatory oscillatory markers of temporal prediction change with age. To this end, 20 right-handed younger adults (14 females, age = 25.4 ± 4.13 years) and 20 right-handed older adults (13 females, age = 60.35 ± 3.92 years) performed a temporal prediction task while 64-channel EEG was recorded. In the task, a visual stimulus moved across the screen toward an occluder, disappeared and reappeared after a variable time delay. Participants judged whether the visual stimulus reappeared "too early" or "too late." Results indicated comparable temporal prediction performance between younger and older adults. We observed a stronger task-related decrease of beta activity in older compared to younger adults. Further, we observed phase adjustments of ongoing delta activity aligning with the disappearance of moving stimuli which was stronger in older compared to younger adults. Together, these observations provide several new insights into the neural dynamics supporting temporal prediction and suggest that neural dynamics associated with temporal prediction appear sensitive to ageing.